An Analytical Approach to Identify Design Criteria for Reducing Earthquake Risks in Residential Interiors - Garip, S. Banu; Garip, Ervin; Birgönül, Zeynep; GÜZELCİ, HANDAN (Istanbul Teknik Universitesi, Faculty of Architecture, 2023)
A vital measure to prevent earthquake risks is to retrofit existing buildings or design and construct resistant structures. After increasing the earthquake resistance of buildings, measures taken in building interiors comes to the forefront. In the scope of this study, comprehensive analytical research is conducted to identify the criteria for reducing earthquake risks in the design of residential interior spaces. Reviewing the literature of both national and international publications using the keywords and phrases “Earthquake and Interior Design” “Earthquake and Furniture Design”, “Earthquake and Architectural Design”, “Earthquake and Materials”, “Precautions for Earthquake Damages”, “Earthquake Psychology” is employed as a method. In the next step, criteria extracted from the content analysis are categorized, analyzed and evaluated systematically. Together with this research, a set of measures to reduce earthquake risks for the interior design of residential interiors was presented. It also includes risks and strategies related to categorized interior elements, which designers can use in the design process. Many people could be inside residences, where most daily life is spent during an earthquake. This describes the study’s widespread impact. The design criteria presented are expected to be a source that includes a set of categorized data with a holistic approach to reduce risks, leading to safe design, and ensuring up-to-date continuity of knowledge for future designs.
Keywords: Earthquake Risk Reduction; Interior Architecture; Secure Design; Housing Interiors